ROLE OF POSITIVE VALUES AND PERSONALITY TRAITS IN PREVENTING OF PROFESSIONAL BURNOUT AMONG LAW ENFORCEMENT OFFICERS - Iryna Arshava; Anastasiia Baratyns’ka (European Scientific Journal, ESJ, 2015)
Despite the significant increase of scientists’ interest towards investigation of police personnel burnout syndrome diagnostic and psycho prophylaxis problem, the issue study in aspect of positive psychology ideas still remains beyond the researchers’ interests. Based on the fundamental provisions of positive psychology we can assume that certain positive values and its "strong" traits of personality may be the predictors of preventing the emergence of professional burnout among law enforcement officers. The objective of current research was to determine the characteristics of the burnout manifestations among police personnel and to identify the positive values generic to law enforcement officers, as well as to define the role of these values and certain personality traits in prevention of burnout among police officers. Using the r-linear Pearson correlation coefficient on a sample of 180 law enforcement officers enabled the definition of certain personal properties of police personnel which manifestations aggravate in every burnout phase (I – III). The common feature of all burnout phases is manifestation of such personal traits as neurosity, depression, shyness, emotional lability. Also, manifestation of such personality traits as irritability, spontaneous and reactive aggression, openness aggravates in II (“Resistance”) and III (“Exhaustion”) phases of professional burnout. As for police personnel positive values studies, we can assume that high level of "humanity", "wisdom" and "courage" virtues combined with the development of certain personality traits may be the predictors of burnout emergence among law enforcement officers.